Network analysis reveals microbe-mediated impacts of aeration on deep sediment layer microbial communities - Wang, Zhenyu; Liu, Feifei; Li, Enze; Yuan, Yongqiang; Yang, Yonggang; Xu, Meiying; Qiu, Rongliang (Frontiers in Microbiology, 2022)
Over-aeration is a common remediation strategy for black and odorous water bodies, in which oxygen is introduced to impact aquatic microbial communities as an electron acceptor of high redox potential. In this study, black-odorous freshwater sediments were cultured for 9 weeks under aeration to investigate microbial covariations at different depths and time points. Based on community 16S rRNA gene sequencing, the microbial covariations were visualized using phylogenetic microbial ecological networks (pMENs). In the spatial scale, we identified smaller and more compact pMENs across all layers compared with the anaerobic control sediments, in terms of network size, average node connectivity, and modularity. The aerated middle layer had the most connectors, the least module hubs, a network hub, shorter average path length, and predominantly positive covariations. In addition, a significant sulfate accumulation in the aerated middle layer indicated the most intense sulfide oxidation, possibly because aeration prompted sediment surface Desulfobulbaceae, known as cable bacteria, to reach the middle layer. In the time scale, similarly, aeration led to smaller pMEN sizes and higher portions of positive covariations. Therefore, we conclude that elevated dissolved oxygen at the water-sediment interface may impact not only the surface sediment but also the subsurface and/or deep sediment microbial communities mediated by microorganisms, particularly by Desulfobulbaceae.